Common bunt in organic wheat: unravelling infection characteristics relevant for resistance breeding - Lunzer, Magdalena; Dumalasová, Veronika; Pfatrisch, Kilian; Buerstmayr, Hermann; Grausgruber, Heinrich (Frontiers in Plant Science, 2023)
After decades off the radar of breeders and producers, common bunt has re-emerged as a major threat to wheat yield and quality, especially in organic farming. Resistance against its causal agents Tilletia tritici and T. laevis is present in the wheat gene pool and can be deployed in resistance breeding. Molecular markers for resistance loci help to accelerate the time-consuming breeding process and are therefore crucial for the rapid development of resistant cultivars. These provide the most economically efficient and sustainable way to combat the disease since seed treatments approved for organic farming are rare and do not provide full protection. Many aspects of bunt infection characteristics are still unknown or have not been addressed since the mid-20th century when seed treatment was not yet routine. We tested a winter wheat diversity panel with 128 lines for common bunt resistance in Austria and Czechia, and evaluated the applicability of marker-assisted selection (MAS) via Kompetitive Allele-Specific PCR markers in genotypes with high variation in their genetic background. Field trials were conducted across two years and artificially inoculated with local bunt populations. The virulence patterns of these inocula differed between locations and only 15% of the tested genotypes showed stable resistance across test sites. Number and weight of bunt sori relative to the total number and weight of wheat grains in sampled ears revealed that partial infections of ears were frequently appearing. Forty-two breeding lines harboring combinations of four different resistance QTL were developed through MAS. Out of these, a quarter were resistant with a maximum of 5% common bunt incidence. We thereby showed that MAS is a useful tool to speed up the selection of resistant breeding lines even in populations with highly diverse genetic backgrounds in which the availability of informative markers may become scarce. MAS is efficient in pyramiding resistance loci and thereby improving the level of resistance as shown by lines with multiple resistance loci having significantly lower disease incidence. Only six out of 46 tested commercial cultivars and breeding lines showed no infection with common bunt, underlining the present scarcity of bunt-resistant cultivars for organic wheat production.